Anti-Tubercular Activity of Pyrazinamide Conjugates: Synthesis and Structure-Activity Relationship Studies - Wahan, Simranpreet K.; Sharma, Sangeeta; Chawla, Pooja A. (Mini Reviews in Medicinal Chemistry, 2023)
Tuberculosis (TB) is an airborne infection caused by the bacteria Mycobacterium Tuberculosis (MTB). It mainly affects the lungs and causes severe coughing, fever, and chest pains. With the rising prevalence of drug-resistant and inactive Tuberculosis (TB), there is an essential need to discover more effective molecules capable of combating this heinous illness. Pyrazinamide is a first-line tuberculosis therapy that shortens prophylactic duration from twelve to six months. The majority of presently used tuberculosis medications were found by a mix of serendipity and innovative chemical alterations of an existing lead drug. Given that the majority of these discoveries occurred years ago, there is a definite need to use fresh methodologies and technology for discovery to meet the grave danger posed by tuberculosis and the rise of treatment resistance strains. Although current research has provided significant insight into TB transmission, diagnosis, and treatment in the last four years, much more progress is needed to successfully reduce tuberculosis prevalence and eventually eradicate it. The disease continues to be a public health concern, second only to HIV/AIDS in high fatality rates. This review focuses on current efforts to translate the anti-tubercular activity of all known pyrazinamide analogues and proposes a novel approach for developing new anti-tubercular drugs based on the fusion of pyrazinamide with various heterocyclic rings that shorten treatment for drug-sensitive and multidrug-resistant tuberculosis.
Keywords: Synthetic schemes